Hydrogel‐Based Actuators: Heterogeneous Hydrogel Structures with Spatiotemporal Reconfigurability using Addressable and Tunable Voxels (Adv. Mater. 10/2021). Issue 10 (9th March 2021) - Khodambashi, Roozbeh; Alsaid, Yousif; Rico, Rossana; Marvi, Hamid; Peet, Matthew M.; Fisher, Rebecca E.; Berman, Spring; He, Ximin; Aukes, Daniel M.
Abstract : Assembly of small‐scale soft robots using hydrogelbased soft voxel actuators (SVAs) facilitates the actuation of complex and hyper‐redundant motion. In article number 2005906, Ximin He, Daniel M. Aukes, and co‐workers report the electrical activation of SVAs, which resembles the activation of muscle tissue via electrical impulses in the nervous system, as in soft‐bodied animals such as the octopus. Rendering by Cole Brauer.